Recurrence patterns and impact of brain metastases in synchronous single organ oligometastatic lung cancer following local ablative treatment – A multicenter analysis. (August 2022) - Frost, Nikolaj; Roeper, Julia; Velthaus, Janna-Lisa; Raspe, Matthias; Olive, Elisabeth; Schmittel, Alexander; Schmidt, Bernd; Wasilewski, David; Onken, Julia; Lüders, Heike; Witzenrath, Martin; Senger, Carolin; et al.
Highlights: Local ablative therapy (LAT) improves survival in oligometastatic lung cancer (OMD) Retrospective multicenter analysis from 5 certified German Lung Cancer centers. The initial metastatic site determines the pattern of relapse. Subsequent LAT for every recurrence is feasible for 25% of all patients. Intracranial disease control determines survival and correlates to (repeated) LAT. Abstract: Introduction: Local ablative therapy (LAT) improves survival in oligometastatic lung cancer (OMD), but there is limited information on recurrence patterns, re-treatments and in particular the role of brain metastases during the course of disease. We therefore conducted a retrospective multicenter analysis to evaluate course of disease, sequence of therapies and predictors for long-term disease-control in the brain and survival endpoints. Patients and methods: Clinical data of patients with synchronous, single organ OMD with ≤4 metastases were collected from 5 certified German lung cancer centers. All patients underwent thorough initial staging including a 18 FDG-PET/CT scan, brain imaging and mediastinal staging, if necessary, and received LAT to all sites of disease. Results: In total, 164 patients were included (median age 62 years [range 41–84], non-squamous histology 80%, N0-1 64%, single metastasis 84%), 103 had brain (cohort A), 61 extracranial metastases (cohort B). With a median follow-up of 66 months, 115 patients (70%) experienced recurrent disease with a different distribution of sites: In cohort A vs. B, brain relapses occurred in 56% vs. 18% and new distant metastases in 5% vs. 40%. In total, LAT for every relapse was possible for 25% (29/115) of the patients. Patients with initial and secondary onset brain metastases experienced long-term disease-control in the brain and subsequently favorable survival with the application of repeated LAT (disease in the brain controlled vs. not-controlled, HR 0.21, p < 0.001). Comparable long-term overall survival was observed in patients with no or isolated brain relapses (5-years OS 74% and 92%) in contrast to patients with extracranial relapses (5-years OS 19.6%, p < 0.001). Conclusions: Repeated LAT for recurrent synchronous single organ OMD results in a long-term favorable outcome. Disease control in the brain appears crucial and likely determines survival.